Adsorption of metal adatoms on single-layer phosphorene. Issue 2 (20th November 2014) - Kulish, Vadym V.; Malyi, Oleksandr I.; Persson, Clas; Wu, Ping
Abstract : We present a first-principles study on the surface reactivity of single-layer phosphorene. Abstract : Single- or few-layer phosphorene is a novel two-dimensional direct-bandgap nanomaterial. Based on first-principles calculations, we present a systematic study on the binding energy, geometry, magnetic moment and electronic structure of 20 different adatoms adsorbed on phosphorene. The adatoms cover a wide range of valences, including s and p valence metals, 3d transition metals, noble metals, semiconductors, hydrogen and oxygen. We find that adsorbed adatoms produce a rich diversity of structural, electronic and magnetic properties. Our work demonstrates that phosphorene forms strong bonds with all studied adatoms while still preserving its structural integrity. The adsorption energies of adatoms on phosphorene are more than twice higher than on graphene, while the largest distortions of phosphorene are only ∼0.1–0.2 Å. The charge carrier type in phosphorene can be widely tuned by adatom adsorption. The unique combination of high reactivity with good structural stability is very promising for potential applications of phosphorene.